The Sports Health Education: Injury Treatment in Karate Training in Pekanbaru City - Salsabilah Salsabilah; Rahmad Diyanto; Agung Hilmi Wahdi; Sri Agustina Ratnawati; Ria Rafianti; Hirja Hidayat (CV. AFDIFAL MAJU BERKAH, 2026)
This community service activity aims to improve the knowledge and skills of karate athletes in preventing and treating sports injuries, particularly through education on injury care using the RICE method (Rest, Ice, Compression, Elevation). The methods used are educational and participatory, including interactive lectures, demonstrations and practical workshops on RICE, discussions and question and answer sessions, and evaluation through interviews. Participants consisted of 29 karate athletes from various clubs in Pekanbaru. The results of the activity showed enthusiasm and active participation from the participants. Based on observations and interviews, there was an increase in understanding of common types of injuries (such as sprains, bruises, muscle strains, and cramps) as well as an increase in psychomotor skills and confidence in performing first aid independently using the RICE principle. It was concluded that this sports health education programme was effective in equipping athletes with theoretical knowledge and practical skills to handle injuries, reduce the risk of severity, and support the continuity of safe training. Similar education is urgently needed given the low level of sports health literacy among novice and adolescent karate athletes